Sputtered vanadium carbon nitride (VCN) thin films: a potential electrode for supercapacitors - G Vijaya Prasath; J Vivekanandan; M Selvamurugan; K S Usha; P Sakthivel; G Anandha Babu; G Ravi (Materials Research Express, 2024)
The preparation of efficient thin film-based electrode materials is a vital prerequisite for practical energy storage devices. Herein, we have prepared unique vanadium carbon nitride (VCN) thin films on FTO substrates by pulsed DC magnetron sputtering technique for competent supercapacitor electrodes. XRD analysis confirmed the crystalline nature of VCN thin films. SEM and AFM revealed a smooth morphology with an average grain size of 30 nm. Raman spectra showed two broad peaks around 1346 and 1589 cm ^−1 , belonging to the D-band and G-band of VCN. The surface electronic states of VCN were investigated by XPS analysis, which confirmed the formation of pure VCN films without any impurities. The electrochemical performance of the thin film electrode was evaluated using cyclic voltammetry (CV), Galvanostatic charge–discharge (GCD), and Electrochemical impedance analysis (EIS). The electrochemical results showed the VCN thin films exhibited super capacitive behaviours. The maximum specific capacitance (Cs) value of 78.2 F g ^−1 was obtained from GCD studies. A variation in charge transfer resistance is detected from the EIS study, which arises due to the partial oxidation of the active nitride component. The VCN electrode showed good cycling stability, retaining 87% of its capacitance at a current density of 5 A g ^−1 even after 2000 cycles. The sputtered VCN films have been demonstrated as potential thin film electrodes for electrochemical supercapacitors for practical energy storage devices.